Immobilization of 3-hydroxybenzoate 6-hydroxylase onto functionalized electrospun polycaprolactone ultrafine fibers: A novel heterogeneous catalyst - Tiyaporn Srisook (2018)
3-Hydroxybenzoate 6-hydroxylase (3HB6H), an enzyme that catalyzes regiospecific para-hydroxylation of aromatic compounds, was successfully immobilized onto electrospun polycaprolactone (PCL) ultrafine fibers (424 ± 99 nm in diameter). The fibers were fabricated from 13% w/w PCL (MW ∼8 × 104g/mol) dissolved in a mixed solvent of formic acid (25% v/v) and acetic acid (75% v/v) at an applied voltage of 16 kV and a fiber collection distance of 12.5 cm. Before being immobilized with 3HB6H, the surface of electrospun PCL fibers was functionalized by reacting with ethylenediamine activated with 5% v/v glutaraldehyde using aluminum sulfate as a catalyst. Effects of the immobilization process on pH tolerance and thermal stability of 3HB6H were investigated. Results indicated that 3HB6H immobilized onto PCL fibers could tolerate the changes in temperature and pH better than the free enzyme could. Therefore, the 3HB6H-immobilized PCL fibers are potentially useful as a heterogeneous catalyst under the conditions in which free 3HB6H could not endure. © 2014 Elsevier Ltd. All rights reserved.